Respon Hasil Kakao (Theobroma Cacao L.) Pada Pemangkasan Tanaman dan Sistem Tanam Dengan Koro Pedang (Canvalia ensiformis L.) - Edo, Hermanus; Sunaryo, Yacobus; Prasetyowati, Sri Endah; Sutardi (JURNAL ILMIAH AGROUST, 2022)
The purpose of the study was to determine the effect of pruning and land use under shelter using a planting system on the response of cocoa yields (Theobroma cacao L.) and the vegetative growth component of jack bean (Canavalia ensiformis L.) carried out from Juny 1 to August 31, 2021 in Plosokerep, Patuk, Gunung Kidul, Yogyakarta Special Region. The study experiment arranged a Split Plot Design, the main plot of the planting system (monoculture and intercropping) and the pruning plot children, namely without pruning, 30% pruning, and 60% pruning. The results showed that there was no interaction between the planting system and pruning the vegetative growth variables of cocoa plants, but the treatment of the planting system, namely, monocultures produced a lower dry seed weight than intercropping on the cocoa yield variable and pruning had no effect on the variable components of jack bean growth.